Self-control has a social role in primates, but not in other mammals or birds - R. I. M. Dunbar; Susanne Shultz (Scientific Reports)
Abstract The capacity to inhibit prepotent actions (strategic self-control) is thought to play an important role in many aspects of the behaviour of birds and mammals. Though widely considered important for foraging decisions, inhibition is also crucial for maintaining the temporal and spatial coherence of bonded social groups. We analyse four different sets of comparative experimental data on primates to show (1) that tasks widely assumed to index inhibition segregate naturally into two distinct clusters (those that involve strategic self-control and those that might be better described as detour or causal reasoning tasks) and (2) that, across primate species, the former tasks correlate better with the demands of social contexts, while the latter correlate better with the demands of foraging contexts. Finally, using a wider sample of mammals and birds, we show (3) that the capacity for (strategic) self-control is unique to anthropoid primates (as suggested by the Passingham-Wise Conjecture). We propose that strategic inhibition may be neurologically costly (and hence taxonomically rare) because animals have to model two different views of the world at the same time and prevent one leaking into the other. We conclude, first, that future studies need to examine the cognitive demands of the tasks they use more carefully and avoid misusing terms to label phenomena that involve very different demand characteristics and, second, that more attention is given to neuroimaging studies that examine the neural activity involved in different tasks.